"I'm Not the Only Writer in The Room": A Framework for Co-Creating Confident Writing Classrooms - McConnel, Jen; Beach, Pamela (Language and Literacy / Langue et littératie, 2021)
This study is rooted in social cognitive theory, specifically Bandura's work on self-and collective efficacy. The authors explore self reported confidence levels with writing instruction from secondary teachers across subjects in Canada and the United States by pairing a self-efficacy scale developed by Locke and Johnston (2016) with semi-structured interviews conducted via Skype. 60 teachers participated in the survey, with 25 from Canada and 35 from the United States. Although teachers report relatively strong levels of self efficacy in writing instruction, the responses of participants regarding collective efficacy are more mixed. Based on these results, coupled with six interviews (split evenly between teachers in Canada and the United States), the authors propose a framework to help teachers of all subject areas increase their confidence in writing instruction while also helping students develop their own confidence as writers. This three-pronged framework of identity, context, and authority, relies on co-creating community with students. The potential of this framework is creative, offering teachers (and students) multiple ways into a conversation about writing that will not only enhance confidence, but will create a classroom culture in which diverse writing strategies and perspectives are valued.